A study on selective surface nitridation of TiO 2 nanocrystals in the afterglows of N 2 and N 2 -O 2 microwave plasmas - Jeon, Byungwook; Kim, Ansoon; Ricard, André; Sarrette, Jean Philippe; Yu, Xiaomei; Kim, Yu Kwon (Applied Surface Science, 2018)
Surface-selective chemical modification of anatase TiO 2 nanocrystals is performed in the post-discharge region of N 2 microwave plasma and the chemical bonding states of surface nitrogen species are carefully evaluated using X-ray photoemission spectroscopy (XPS). It is found that the surface treatments in the afterglows induce the formation of stable nitrogen species at or near the surface of TiO 2 . Interestingly, the detailed bonding structure varies strongly depending on the afterglow condition. In pure N 2 afterglows, various N species with a direct Ti–N bond are formed on the surface, while the use of N 2 -O 2 mixtures induces the formation of additional oxidized species of NO 3 − on the surface. This is attributed to the high concentrations of O or NO in the afterglows of N 2 -O 2 plasmas. The incorporation of substitutional N species in the subsurface is also achieved after a prolonged exposure in the early afterglow with a high density of N 2 + species. Our results show that the exposure condition can be controlled for a selective chemical modification of TiO 2 surface for the control of surface properties in various applications.
Keywords: Afterglow; Chemical bonding state; Exposure conditions; Microwave plasma; Selective surface; TiO2; TiO2 nanocrystals; X ray photoemission spectroscopy; Afterglow; Microwave plasma; N 2; Surface modification; TiO 2